Metodologias ativas e mídias digitais no ensino médio: um estudo diagnóstico em língua portuguesa de uma escola pública de Alegrete, RS - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This article examines how active learning methodologies, mediated by digital media, can expand learning opportunities for first-year high school students in the Portuguese Language component of a public school located in the outskirts of Alegrete, Rio Grande do Sul. A qualitative, exploratory, and descriptive approach was adopted, combining a literature review with the application of an online questionnaire to four teachers. Content analysis (Bardin, 2011) guided the organization of the data into four thematic axes: infrastructure and access, teacher training and pedagogical use of digital media, perceptions of active methodologies, and alignment with the BNCC. The findings indicate the presence of basic technological resources, though limited by connectivity constraints; gaps in continuing education and institutional policies; a favorable perception among teachers regarding the use of digital media to promote authorship and student engagement; and potential alignment with BNCC competencies, particularly Digital Culture and Work and Life Project. It is concluded that the articulation between active learning methodologies and digital media supports multiliteracy practices and student protagonism, but requires investments in infrastructure, teacher training, and evaluative instruments to convert potentialities into demonstrable learning outcomes.
Active methodologies and digital media in high school education: a diagnostic study in Portuguese language at a public school in Alegrete, RS
Keywords: Metodologias ativas; Mídias digitais; Lingua portuguesa; Active learning methodologies; Digital media; Portuguese language; CIENCIAS SOCIAIS APLICADAS